A Newly Identified lncBCAS1-4_1 Associated With Vitamin D Signaling and EMT in Ovarian Cancer Cells - Xue, Yaqi; Wang, Ping; Jiang, Fei; Yu, Jing; Ding, Hongmei; Zhang, Zengli; Pei, Hailong; Li, Bingyan (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) has been identified rapidly due to the important role of lncRNAs in many biological processes and human diseases including cancer. Vitamin D compounds are supported to be applied as preventative and therapeutic anti-cancer agents. However, the expression profile of lncRNAs regulated by 1alpha,25-dihydroxyvitamin D3 [1alpha,25(OH)2D3] in ovarian cancer remains to be clarified. In the present study, we identified 244 differentially expression (DE) lncRNAs and 102 DE mRNAs by our microarray data. GO and KEGG pathway analysis indicated that the DE genes were mainly enriched in TGF-beta, MAPK, Ras, PI3K-Akt and Hippo signaling pathways, as well as vitamin D-related pathway. We further assessed the potential lncRNAs linking vitamin D signaling with EMT, and lncBCAS1-4_1 was identified. Moreover, we found the most upregulation lncBCAS1-4_1 has 75% transcripts same to CYP24A1, metabolic enzyme of 1alpha,25(OH)2D3. Finally, we established lncBCAS1-4_1 gain-of-function cell models and demonstrated that knockdown of lncBCAS1-4_1 inhibited proliferation and migration of ovarian cancer cells by regulating EMT-related mRNAs. Furthermore, our results also indicated that high lncBCAS1-4_1 obviously resisted the anti-tumor effect of 1alpha,25(OH)2D3 by upregulating ZEB1. These data will provide new evidence that lncRNAs are served as a target for the anti-tumor of 1alpha,25(OH)2D3.